What Happens to Nutrition Intake in the Post–Intensive Care Unit Hospitalization Period? An Observational Cohort Study in Critically Ill Adults. Issue 1 (20th June 2018) - Ridley, Emma J.; Parke, Rachael L.; Davies, Andrew R.; Bailey, Michael; Hodgson, Carol; Deane, Adam M.; McGuinness, Shay; Cooper, D. James
Abstract: Background: Little is currently known about nutrition intake and energy requirements in the post–intensive care unit (ICU) hospitalization period in critically ill patients. We aimed to describe energy and protein intake, and determine the feasibility of measuring energy expenditure during the post‐ICU hospitalization period in critically ill adults. Methods: This is a nested cohort study within a randomized controlled trial in critically ill patients. After discharge from ICU, energy and protein intake was quantified periodically and indirect calorimetry attempted. Data are presented as n (%), mean (SD), and median (interquartile range [IQR]). Results: Thirty‐two patients were studied in the post‐ICU hospitalization period, and 12 had indirect calorimetry. Mean age and BMI was 56 (18) years and 30 (8) kg/m 2, respectively, 75% were male, and the median estimated energy and protein requirement were 2000 [1650–2550] kcal and 112 [84–129] g, respectively. Oral nutrition either alone (n = 124 days, 55%) or in combination with enteral nutrition (n = 96 days, 42%) was the predominant mode. Over 227 total days in the post‐ICU hospitalization period, a median [IQR] of 1238 [869–1813] kcal and 60 [35–89.5] g of protein was received from nutrition therapy. In the 12 patients who had indirect calorimetry, the median measured daily energy requirement was 1982 [1843–2345] kcal and daily energy deficit was −95 [−1050 to 347] kcal compared with the measured energy requirement. Conclusions: Energy and protein intake in the post‐ICU hospitalization period was less than estimated and measured energy requirements. Oral nutrition provided alone was the most common mode of nutrition therapy.